Effect of Attributions on Consumer Response to CSR Efforts with Consumer Trust as the Moderator - Samuel Dio Gyver; SeTin SeTin (Indonesian Journal of Sustainability Accounting and Management, 2022)
This study aims to examine the effect of other and self-serving attributions on the consumer response to corporate social responsibility (CSR) efforts with consumer trust as the moderator. This study also examines the differences in perceptions between men and women in assessing the motives of CSR efforts. Data were collected through a questionnaire survey of 122 students at a private university in Bandung. Multiple linear regression, independent simple T-Test, and F test were used for data analysis. Results prove that other-serving attributions have a positive effect on consumer response to CSR efforts. Meanwhile, self-serving attributions have a negative effect on consumer response to CSR efforts. When moderated by consumer trust in the firm, other-serving attributions will increase the consumer response to CSR efforts, whereas self-serving attributions will further reduce the consumer response to CSR efforts. Differences in perceptions are found between men and women regarding the consumer response to CSR efforts. This study implies that the development of CSR efforts needs to consider attributions and consumer trust in the firm.